A retrospective assessment of metropolitan religious adherence rate, individual and neighborhood social capital and their impact on women’s health - Kim Nichols Dauner; Neil A. Wilmot (BMC Public Health, 2019)
Abstract Background Social capital is a multilevel construct impacting health. Community level social capital, beyond the neighborhood, has received relatively less attention. Moreover, the measurement of community level social capital has tended to make use of aggregated individual data, rather than observable community characteristics. Methods Herein, metropolitan religious adherence, as an observable community-level measure of social capital, is used. We match it to city of residence for 2826 women in the Fragile Families Childhood Wellbeing Study (a cohort study) who have lived continuously in that city during a nine-year period. Using ordered logistic regression with clustered standard errors to account for area effects, we look at the relationship between metropolitan religious adherence and self-rated health, while controlling for lagged individual, neighborhood, and socioeconomic factors, as well as individual level religious attendance. Results Religious adherence at the community level is positive and statistically significant; every 1% increase in area religiosity corresponds to a 1.2% increase in the odds of good health. Conclusions These findings shed light on a possible pathway by which social capital may improve health, perhaps acting as a stress buffer or through spillover effects of reciprocity generated by exposure to religion.